COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF DIGITAL BANKS DURING THE COVID-19 PANDEMIC - Rachmaniyah, Fatichatur; Purwati, Titik (SYNTIFIC, 2023)
Background. Along with the development of technology, banking services in Indonesia have largely transitioned into Digital Banks. Digital banks have become a solution to economic problems during the pandemic period. Research Purpose. To determine the analysis of the differences in the financial performance of digital banks during the COVID-19 pandemic period. Research Method. The research employs a comparative quantitative approach with a case research design. The research objects are three digital banks, namely Jago Bank, BTPN Bank, and Bukopin Bank. The data used in the research consists of financial reports from the quarters of the years 2020-2021. The research variables include the ratios ROA, ROE, BOPO, NPM, DER, and LDR. The analysis method utilizes the ANOVA test. Findings. The financial performance in terms of ROA, ROE, BOPO, NPM, and DER ratios between Jago Bank and BTPN Bank showed significant differences. However, the LDR ratio was no significant difference. The financial performance between Jago Bank and Bukopin Bank, in terms of the ROA, ROE, NPM, and DER ratios, resulted in significant differences. However, the BOPO dan LDR ratios were no significant differences. The overall ratios of BTPN Bank & Bukopin Bank have a significant difference. Conclusion. There is a significant difference in financial performance between Jago Bank, BTPN Bank, and Bukopin Bank during the pandemic period. These three digital banks exhibit different financial performances, aligning with their respective areas of focus. However, there are some variables among these digital banks that did not show significant differences in the LDR and BOPO.